Design and Analysis of Tooth Impact Test Rig for Spur Gear - Wafiuddin, Md Ghazali; Ismail Ali, Abdul Aziz; Daing Mohamad Nafiz, Daing Idris; Nurazima, Ismail; Azizul Helmi, Sofian (IOP Publishing, 2016)
This paper is about the design and analysis of a prototype of tooth impact test rig for spur gear. The test rig was fabricated and analysis was conducted to study its' limitation and capabilities. The design of the rig is analysed to ensure that there will be no problem occurring during the test and reliable data can be obtained. From the result of the analysis, the maximum amount of load that can be applied, the factor of safety of the machine, the stresses on the test rig parts were determined. This is important in the design consideration of the test rig. The materials used for the fabrication of the test rig were also discussed and analysed. MSC Nastran Patran software was used to analyse the model, which was designed by using SolidWorks 2014 software. Based from the results, there were limitations found from the initial design and the test rig design needs to be improved in order for the test rig to operate properly.